Substituted alkenediols by alkylative double ring opening of dihydrofuran and dihydropyran epoxides. - Hodgson, D; Stent, M; Wilson, F (2001)
[reaction: see text]. Dihydrofuran and dihydropyran epoxides undergo alkylative double ring opening with organolithiums to provide a new route to substituted alkenediols.